Decomposing the German East–West wage gap1. Issue 1 (23rd October 2017) - Kluge, Jan; Weber, Michael
Abstract: Wages in East Germany are persistently lower than in West Germany. We study the micro‐level determinants of this spatial wage gap, using an Oaxaca–Blinder decomposition and rich linked employer–employee data. In total, up to one half of the aggregate wage differential can be attributed to structural differences in worker, establishment and regional characteristics. Regional price and establishment size differentials alone account for one quarter of the wage gap at the median. Price level differentials are even more relevant towards the top of the wage distribution. Towards the bottom, differences in union coverage become more important. Our findings are quite stable over the period from 1996 to 2010.